Assessment of Pupils’ Personal Achievements - T. A. Strokova (Образование и наука)
The implementation of the new state educational standards, based on the competence approach, requires some new criteria, procedures and diagnostic tools for estimating pupils’ personal achievements. However, there is a lack of necessary guidelines and recommendations for such objective evaluation and comparative analysis of the effectiveness of educational establishments. The urgent need for unified monitoring instruments induced the author to develop a criteria-diagnostic complex providing the options for evaluating the important personal development aspects – intellectual, value-oriented and moral. The author recommends a self-assessment method for evaluating the intellectual qualities (i.e. self-dependency, critical thinking, logics, flexibility, depth, originality, etc.), intellectual competences, and moral traits. The method is based on the tests – «Pupil in his own eyes» and «Pupil in the expert teachers’ eyes». For examining the value orientation, the author takes the classical method by M. Rokich. The approbation of the complex evaluation method was carried out in Tyumen schools and lyceums regarding the last year pupils. The research findings and proposed assessment tools can be used by headmasters and school teachers for monitoring the pupils’ personal growth.